A cross-reactive neutralizing monoclonal antibody protects mice from H5N1 and pandemic (H1N1) 2009 virus infection - Sakabe, Saori; Iwatsuki-Horimoto, Kiyoko; Horimoto, Taisuke; Nidom, Chairul A.; Quynh Le, Mai thi; Takano, Ryo; Kubota-Koketsu, Ritsuko; Okuno, Yoshinobu; Ozawa, Makoto; Kawaoka, Yoshihiro (Antiviral research, 2010)
A novel influenza (H1N1) virus caused an influenza pandemic in 2009, while highly pathogenic H5N1 avian influenza viruses have continued to infect humans since 1997. Influenza, therefore, remains a serious health threat. Currently, neuraminidase (NA) inhibitors are the mainstay for influenza therapy; however, drug-resistant mutants of seasonal H1N1 and H5N1 viruses have emerged highlighting the need for alternative therapeutic approaches. One such approach is antibody immunotherapy. Here, we show that the monoclonal antibody C179, which recognizes a neutralizing epitope common among H1, H2, H5, and H6 hemagglutinins (HAs), protected mice from a lethal challenge with various H5N1 and pandemic (H1N1) 2009 viruses when administered either intraperitoneally or intranasally. The protective efficacy of intranasally inoculated C179 was comparable to that of intraperitoneal administration. Our results suggest that direct administration of this anti-influenza antibody to viral replication sites is an effective strategy for prophylaxis and therapy.